Relative importance of certain factors affecting the thermal environment in subway stations based on field and orthogonal experiments. (May 2020) - lv, Wenchao; Li, Angui; Ma, Jiangyan; Cui, Haihang; Zhang, Xin; Zhang, Wenrong; Guo, Yongzhen
Abstract: As subway stations in cold-climate regions typically have no heating systems, passengers often feel cold in such stations during winter. People desire a comfortable thermal environment, which is sensitive to certain factors. Therefore, identifying the key influencing factors is fundamental for improving thermal environment. In this study, two environmental factors (outdoor temperature and soil temperature) and four factors concerning operation conditions (train interval, platform screen door opening area, ridership, and the number of open piston vent shafts) were analyzed. An orthogonal experimental design was applied to efficiently identify influencing factors, assisted by field test and numerical study. Through range analysis and analysis of variance, it was discovered that the outdoor temperature and soil temperature were significant to the concourse environment and platform environment, respectively. Moreover, the analyses revealed the separate rankings of the relative importance of factors for the concourse environment and platform environment. Using these rankings, targeted strategies could be proposed more effectively for the controllable influencing factors in future research. The orthogonal experimental design is an efficient alternative to qualitative information collection for complex subway systems. This study provides new insights into subway thermal environment in winter, and is helpful in creating a more comfortable thermal environment.